Preparation process of hard carbon material for negative electrode of sodium-ion battery
Through the composite process of nitrogen doping and Sn4P3 alloy nanomaterials, a high-magnification and cyclic stable Sn4P3@NC composite glucose-based hard carbon material was prepared, which solved the problem of high initial irreversible capacity of hard carbon anode materials and was suitable for sodium ion batteries. Highly efficient electrochemical performance and low cost preparation are achieved.
Patent Information
- Application Number
- CN202411254019.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-03
AI Technical Summary
The initial irreversible capacity of existing hard carbon anode materials in lithium-ion batteries has resulted in low efficiency for the first time, limiting its large-scale industrial application in electric vehicles and unable to meet the demand for large-scale charging.
The composite process of nitrogen-doped glucose-based hard carbon material and Sn4P3 alloy nanomaterial was adopted to prepare glucose-based hard carbon precursors by hydrothermal method, and Sn4P3@NC composite glucose-based hard carbon material was prepared by ball milling to improve the surface moisturization of the material. Wetness and electrochemical properties.
It significantly improves the ratio and circulation performance of the material, reduces the preparation cost, provides good low-temperature performance and high energy density, extends the number of electrochemical reactions, and is suitable for the negative electrode of sodium ion battery.
Smart Images

Figure CN119252880A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation process of a hard carbon material for a negative electrode of a sodium ion battery. Background Art
[0002] In recent years, people have invested a lot of energy in the research and development of negative electrode materials for lithium-ion batteries to replace traditional graphite negative electrode materials with low theoretical capacity. As a negative electrode material for lithium-ion batteries, hard carbon has high gram-to-weight capacity, excellent rate performance and low-temperature performance, and is low-cost and widely available. It has received extensive attention and research from the scientific and industrial communities. However, the initial irreversible capacity of hard carbon negative electrode materials is currently very high, resulting in low first coulombic efficiency, which restricts its large-scale industrial application in lithium-ion batteries. Hard carbon negative electrode materials have a wide range of sources and a variety of precursors. Biomass, small molecules and high molecular polymers can all be used as precursors for hard carbon negative electrode materials, and hard carbon negative electrode materials can be obtained by heat treatment. The type of precursor and the heat treatment process have a very important influence on the structure and electrochemical properties of hard carbon negative electrode materials.
[0003] At present, hard carbon materials are the most widely used negative electrode materials for lithium-ion batteries in the market, among which graphite occupies the largest market share. Graphite has achieved great success with its long cycle life, stable voltage platform and low manufacturing cost. However, graphite cannot meet the high-rate charging required by electric vehicles, so finding and preparing new high-rate negative electrode materials has become one of the hot issues in current research. Summary of the invention
[0004] In view of the above problems, the present invention provides a hard carbon material for a negative electrode of a sodium ion battery.
[0005] The first technical purpose of the present invention is to provide a preparation method for nitrogen-doped glucose-based hard carbon material.
[0006] The second technical purpose of the present invention is to provide a method for preparing Sn4P3 alloy nanomaterials.
[0007] The third technical objective of the present invention is to provide a Sn4P3@NC composite glucose-based hard carbon material.
[0008] The present invention provides a hard carbon material for a negative electrode of a sodium ion battery, comprising the following steps: preparation of a glucose-based hard carbon precursor, preparation of a nitrogen-doped glucose-based hard carbon precursor, preparation of a nitrogen-doped glucose-based hard carbon material, preparation of a Sn4P3 alloy nanomaterial, and preparation of a Sn4P3@NC composite glucose-based hard carbon material.
[0009] Preferably, step (1) preparation of glucose-based hard carbon precursor Glucose and water are mixed to obtain a glucose solution, and then the glucose solution and water are added to a stainless steel high-pressure reactor in a certain mass ratio, hydrothermally reacted at a certain temperature, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate is dried in a forced air drying oven to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor The glucose-based hard carbon precursor prepared in step (1) is dissolved in deionized water, stirred vigorously at room temperature, then formaldehyde solution is added dropwise, stirred at room temperature, and then tannic acid (TA) is slowly added, stirred at room temperature, collected by centrifugation in a high-speed centrifuge, washed with deionized water, and then the sample is transferred to a freeze dryer for drying. Subsequently, carbonization is carried out in a high-temperature tubular heating furnace, nitrogen is introduced as a protective gas, and the carbonization temperature, holding time, and carbonization heating rate are set to finally obtain a nitrogen-containing glucose-based hard carbon precursor; Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) is ground into powder and placed in a crucible. After installation, the vent valve is opened and an inert gas (argon) is slowly introduced to ensure that the air in the cavity is exhausted. Carbonization is performed in an argon atmosphere in a tubular furnace. Finally, a carbonization heating program is set: keep warm at a certain temperature, and finally cool to room temperature at a certain rate. After the cavity is cooled, the NC-T hard carbon material (nitrogen-doped glucose-based hard carbon material) is taken out; Step (4) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for later use, the red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then transferred to a glove box after freeze drying. The special water-free and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. An appropriate amount of red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. Using an ideal molar ratio, a certain mass ratio of Sn and P elemental powder is calculated and weighed using an electronic balance and placed for later use. Then, zirconium beads are weighed according to the ball-to-material mass ratio and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protection process. Finally, the parameters of the micro planetary ball mill are set. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use. Step (5) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a certain ball-to-material mass ratio, and Sn4P3 and the nitrogen-doped glucose-based hard carbon precursor are compounded in a certain mass ratio. Under the condition of keeping the ratio unchanged, the pyrolysis temperature of the hard carbon is changed, the ball mill is sealed and filled with inert gas for protection process, and then sealed and ventilated. Finally, the power is turned on, and after working for a certain period of time, the Sn4P3@NC composite glucose-based hard carbon material is obtained.
[0010] The first technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (1) preparation of glucose-based hard carbon precursor Mix 2.5-3g of glucose and 7.5-8g of water to obtain a 25-30% glucose solution, then add the 25-30% glucose solution and water in a mass ratio of 15:85-20:90 (i.e. 56.67-61.2g of water) into a stainless steel high-pressure reactor, perform hydrothermal reaction at 240-260°C for 4-5 hours, cool naturally to room temperature, wash with deionized water and filter to neutrality, and dry the obtained solid precipitate in a forced air drying oven for 24-28 hours to obtain a glucose-based hard carbon precursor.
[0011] The advantages of the present invention are that the hydrothermal method is used to prepare the glucose precursor, which makes the preparation process simpler and more convenient, and the use of glucose to make the hard carbon precursor makes the preparation cost cheaper, and the glucose hard carbon precursor has good cycle stability, electrochemical properties, excellent rate performance and low temperature performance, and is low in cost and widely available, providing good basic performance for the subsequent steps of preparing composite hard carbon materials.
[0012] Preferably, step (2) preparation of nitrogen-doped glucose-based hard carbon precursor Take 0.04-0.06 g of the glucose-based hard carbon precursor prepared in step (1) and dissolve it in 80-100 mL of deionized water. Stir vigorously at room temperature, then drop 120-150 μl of formaldehyde solution, stir at room temperature for 60-80 min, then slowly add 0.6-0.8 g of tannic acid (TA), stir at room temperature for 20-24 h, collect by high-speed centrifuge, wash with deionized water 3-4 times, and then transfer the sample to a freeze dryer for drying for 24-26 h. Then, carbonize it in a high-temperature tubular heating furnace, introduce nitrogen as a protective gas, the carbonization temperature is 700-1400 ° C, the insulation time is 2-2.5 h, and the carbonization heating rate is 2-3 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor was obtained.
[0013] The advantages of the present invention are that the present invention adopts nitrogen atom doping, which is an effective strategy; nitrogen doping can significantly improve the surface wettability of hard carbon materials and produce additional defects; and the present invention selects tannic acid (TA) as the nitrogen source. TA is a natural plant polyphenol compound with the advantages of being renewable and low in price, and TA contains a large number of phenolic hydroxyl groups in its structure, which can increase active sites for redox reactions, thereby obtaining a nitrogen-doped glucose-based hard carbon precursor with excellent electrochemical properties.
[0014] Preferably, step (3) preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) was ground into powder and placed in a crucible. After installation, the vent valve was opened and inert gas (argon) was slowly introduced for 15-20 minutes to ensure that the air in the cavity was exhausted. Carbonization was carried out in an argon atmosphere in a tubular furnace. Finally, the carbonization temperature program was set: initially 4-5 °C min -1 The heating rate is raised to 800-900℃, kept at this temperature for 1-2h, and finally heated at 4-5℃min -1 The temperature of the cavity was cooled to room temperature at a rate of 1000-1400 °C. After the cavity was cooled, the NC-T hard carbon material (nitrogen-doped glucose-based hard carbon material) was taken out. Under the same carbonization steps, NC-T hard carbon materials were prepared at pyrolysis conditions of 1000-1400 °C.
[0015] The second technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (4) preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for later use. The red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then freeze-dried and transferred to a glove box. The special water-free and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. The red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. An ideal molar ratio of 4:3-6:5 (Sn:P) is used to calculate and use an electronic balance to weigh the Sn and P elemental powders and place them for later use. Then, zirconium beads with a diameter of 5-6 mm are weighed at a ball-to-material ratio of 20:1-40:3, and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protective process. Finally, the parameters of the micro planetary ball mill are set, and the motor speed is selected to be 600-800 rpm. The intermittent working mode is adopted: work 2-3 hours, rest 30-45 minutes, and the effective working time is 24-30 hours. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use.
[0016] The advantage of adopting the present invention is that the Sn4P3 alloy material has the advantage of obtaining a higher energy density at a relatively low working potential. The use of the Sn4P3 alloy material can make the final composite hard carbon material have highly stable electrochemical properties. The present invention uses a simple ball milling method, which makes the preparation process simpler and more cost-effective. The unique self-healing mechanism of Sn4P3 provides high capacity, stabilizes the electrochemical microenvironment around the negative electrode, and prolongs the number of reactions.
[0017] The third technical objective of the present invention is achieved through the following technical solutions: Preferably, step (5) preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1-40:3, and Sn4P3 and nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2-11:4. Under the condition that the ratio remains unchanged, the pyrolysis temperature of the hard carbon is changed, the ball mill is sealed and filled with inert gas for protection process, and sealing and ventilation treatment are performed. Finally, the power is turned on, the motor speed is selected to be 500-600rpm, and an intermittent working mode is adopted: work 2-3h, stop 30-45min, and the effective working time is 4-5h, to obtain Sn4P3@NC composite glucose-based hard carbon material.
[0018] The advantage of adopting the present invention is that a Sn4P3@NC composite glucose-based hard carbon material with high capacity and good electrochemical stability is prepared through a simple ball milling process design, and the dual effects of carbonization process and ball milling high-speed shear are combined to regulate the defect-rich hard carbon material, so that it has outstanding rate and cycle performance. The simple synthesis method through ball milling technology shows the advantages of abundant raw materials, green environmental protection and wide scale.
[0019] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantages that the hydrothermal method is used to prepare the glucose precursor, which makes the preparation process simpler and more convenient, and the use of glucose to make the hard carbon precursor makes the preparation cost cheaper, and the glucose hard carbon precursor has good cycle stability, electrochemical properties, excellent rate performance and low temperature performance, and is low in cost and widely available, providing good basic performance for the subsequent steps of preparing composite hard carbon materials; 2. The present invention has the advantages that the present invention adopts nitrogen atom doping, which is an effective strategy, wherein nitrogen doping can significantly improve the surface wettability of hard carbon materials and produce additional defects; and the present invention selects tannic acid (TA) as a nitrogen source, TA is a natural plant polyphenol compound, which has the advantages of being renewable and inexpensive; and the structure of TA contains a large number of phenolic hydroxyl groups, which can increase active sites for redox reactions, so that a nitrogen-doped glucose-based hard carbon precursor with excellent electrochemical properties is obtained; 3. The advantage of the present invention is that the Sn4P3 alloy material has the advantage of being able to obtain a higher energy density at a relatively low working potential. The Sn4P3 alloy material can make the final composite hard carbon material have highly stable electrochemical properties. The present invention uses a simple ball milling method, which makes the preparation process simpler and more cost-effective. The unique self-healing mechanism of Sn4P3 provides high capacity, stabilizes the electrochemical microenvironment around the negative electrode, and prolongs the number of reactions. 4. The advantage of the present invention is that a high-capacity, electrochemically stable Sn4P3@NC composite glucose-based hard carbon material is prepared through a simple ball milling process design, and the dual effects of carbonization process and ball milling high-speed shear are combined to regulate the defect-rich hard carbon material, so that it has outstanding rate and cycle performance. The simple synthesis method through ball milling technology shows the advantages of abundant raw materials, green environmental protection and wide scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flow chart of a method for preparing a hard carbon material for a negative electrode of a sodium ion battery. DETAILED DESCRIPTION
[0021] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.
[0022] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products. Example 1
[0023] Step (1) Preparation of glucose-based hard carbon precursor 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and water were added to a stainless steel autoclave at a mass ratio of 15:85 (i.e., 56.67 g of water), and hydrothermally reacted at 240 ° C for 4 hours, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor 0.04 g of the glucose-based hard carbon precursor prepared in step (1) was dissolved in 80 mL of deionized water, stirred vigorously at room temperature, and then 120 μl of formaldehyde solution was added dropwise, stirred at room temperature for 60 min, and then 0.6 g of tannic acid (TA) was slowly added, stirred at room temperature for 24 h, collected by high-speed centrifuge, washed with deionized water 3 times, and then transferred to a freeze dryer for drying for 24 h. Then, carbonization was carried out in a high-temperature tubular heating furnace, nitrogen was introduced as a protective gas, the carbonization temperature was 700 ° C, the insulation time was 2 h, and the carbonization heating rate was 2 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor is obtained; Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) was ground into powder and placed in a crucible. After installation, the vent valve was opened and inert gas (argon) was slowly introduced for 15 minutes to ensure that the air in the cavity was completely exhausted. Carbonization was carried out in an argon atmosphere in a tubular furnace. Finally, the carbonization temperature program was set: initially 5 °C min -1 The temperature was raised to 700 °C at a heating rate of 5 °C min -1 The rate is lowered to room temperature, and the NC-700 hard carbon material (nitrogen-doped glucose-based hard carbon material) is taken out after the cavity is cooled; Step (4) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for later use. The red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then freeze-dried and transferred to a glove box. The special anhydrous and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. The red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. An ideal molar ratio of 4:3 (Sn:P) is used to calculate and use an electronic balance to weigh the Sn and P elemental powders and place them for later use. Then, zirconium beads with a diameter of 5 mm are weighed at a ball-to-material ratio of 20:1, and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protective process. Finally, the parameters of the micro planetary ball mill are set as follows: the motor speed is selected to be 600 rpm, and the intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 24 hours. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use. Step (5) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1. Sn4P3 and nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2. Under the condition that the ratio remains unchanged, the pyrolysis temperature of the hard carbon is changed, that is, Sn4P3:NC-700=8:2. The ball mill is sealed and filled with inert gas for a protective process, and then sealed and ventilated. Finally, the power is turned on, the motor speed is selected to be 500rpm, and an intermittent working mode is adopted: work for 2h, rest for 30min, and the effective working time is 4h, to obtain Sn4P3@NC composite glucose-based hard carbon material. Example 2
[0024] Step (1) Preparation of glucose-based hard carbon precursor 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and water were added to a stainless steel autoclave at a mass ratio of 15:85 (i.e., 56.67 g of water), and hydrothermally reacted at 240 ° C for 4 hours, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor 0.04 g of the glucose-based hard carbon precursor prepared in step (1) was dissolved in 80 mL of deionized water, stirred vigorously at room temperature, and then 120 μl of formaldehyde solution was added dropwise, stirred at room temperature for 60 min, and then 0.6 g of tannic acid (TA) was slowly added, stirred at room temperature for 24 h, collected by high-speed centrifuge, washed with deionized water 3 times, and then transferred to a freeze dryer for drying for 24 h. Then, carbonization was carried out in a high-temperature tubular heating furnace, nitrogen was introduced as a protective gas, the carbonization temperature was 800 ° C, the holding time was 2 h, and the carbonization heating rate was 2 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor is obtained; Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) was ground into powder and placed in a crucible. After installation, the vent valve was opened and inert gas (argon) was slowly introduced for 15 minutes to ensure that the air in the cavity was completely exhausted. Carbonization was carried out in an argon atmosphere in a tubular furnace. Finally, the carbonization temperature program was set: initially 5 °C min -1 The heating rate was raised to 800 °C, kept at this temperature for 2 h, and finally heated at 5 °C min -1 The rate is lowered to room temperature, and the NC-800 hard carbon material (nitrogen-doped glucose-based hard carbon material) is taken out after the cavity is cooled; Step (4) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for later use. The red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then freeze-dried and transferred to a glove box. The special anhydrous and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. The red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. An ideal molar ratio of 4:3 (Sn:P) is used to calculate and use an electronic balance to weigh the Sn and P elemental powders and place them for later use. Then, zirconium beads with a diameter of 5 mm are weighed at a ball-to-material ratio of 20:1, and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protective process. Finally, the parameters of the micro planetary ball mill are set as follows: the motor speed is selected to be 600 rpm, and the intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 24 hours. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use. Step (5) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1. Sn4P3 and nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2. Under the condition that the ratio remains unchanged, the pyrolysis temperature of the hard carbon is changed, that is, Sn4P3:NC-800=8:2. The ball mill is sealed and filled with inert gas for a protection process, and then sealed and ventilated. Finally, the power is turned on, the motor speed is selected to be 500rpm, and an intermittent working mode is adopted: work for 2h, rest for 30min, and the effective working time is 4h, to obtain Sn4P3@NC composite glucose-based hard carbon material. Example 3
[0025] Step (1) Preparation of glucose-based hard carbon precursor 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and water were added to a stainless steel autoclave at a mass ratio of 15:85 (i.e., 56.67 g of water), and hydrothermally reacted at 240 ° C for 4 hours, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor 0.04 g of the glucose-based hard carbon precursor prepared in step (1) was dissolved in 80 mL of deionized water, stirred vigorously at room temperature, and then 120 μl of formaldehyde solution was added dropwise, stirred at room temperature for 60 min, and then 0.6 g of tannic acid (TA) was slowly added, stirred at room temperature for 24 h, collected by high-speed centrifuge, washed with deionized water 3 times, and then transferred to a freeze dryer for drying for 24 h. Then, carbonization was carried out in a high-temperature tubular heating furnace, nitrogen was introduced as a protective gas, the carbonization temperature was 900 ° C, the insulation time was 2 h, and the carbonization heating rate was 2 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor is obtained; Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) was ground into powder and placed in a crucible. After installation, the vent valve was opened and inert gas (argon) was slowly introduced for 15 minutes to ensure that the air in the cavity was completely exhausted. Carbonization was carried out in an argon atmosphere in a tubular furnace. Finally, the carbonization temperature program was set: initially 5 °C min -1 The heating rate was raised to 900 °C, kept at this temperature for 2 h, and finally heated at 5 °C min -1The rate of cooling is reduced to room temperature, and the NC-900 hard carbon material (nitrogen-doped glucose-based hard carbon material) is taken out after the cavity is cooled; Step (4) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for later use. The red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then freeze-dried and transferred to a glove box. The special anhydrous and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. The red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. An ideal molar ratio of 4:3 (Sn:P) is used to calculate and use an electronic balance to weigh the Sn and P elemental powders and place them for later use. Then, zirconium beads with a diameter of 5 mm are weighed at a ball-to-material ratio of 20:1, and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protective process. Finally, the parameters of the micro planetary ball mill are set as follows: the motor speed is selected to be 600 rpm, and the intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 24 hours. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use. Step (5) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1. Sn4P3 and nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2. Under the condition of keeping the ratio unchanged, the pyrolysis temperature of the hard carbon is changed, that is, Sn4P3:NC-900=8:2. The ball mill is sealed and filled with inert gas for protection process, and sealed and ventilated. Finally, the power is turned on, the motor speed is selected to be 500rpm, and the intermittent working mode is adopted: work for 2h, rest for 30min, and the effective working time is 4h, to obtain Sn4P3@NC composite glucose-based hard carbon material. Example 4
[0026] Step (1) Preparation of glucose-based hard carbon precursor 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and water were added to a stainless steel autoclave at a mass ratio of 15:85 (i.e., 56.67 g of water), and hydrothermally reacted at 240 ° C for 4 hours, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor 0.04 g of the glucose-based hard carbon precursor prepared in step (1) was dissolved in 80 mL of deionized water, stirred vigorously at room temperature, and then 120 μl of formaldehyde solution was added dropwise, stirred at room temperature for 60 min, and then 0.6 g of tannic acid (TA) was slowly added, stirred at room temperature for 24 h, collected by high-speed centrifuge, washed with deionized water 3 times, and then transferred to a freeze dryer for drying for 24 h. Then, carbonization was carried out in a high-temperature tubular heating furnace, and nitrogen was introduced as a protective gas. The carbonization temperature was 1000 ° C, the holding time was 2 h, and the carbonization heating rate was 2 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor is obtained; Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) was ground into powder and placed in a crucible. After installation, the vent valve was opened and inert gas (argon) was slowly introduced for 15 minutes to ensure that the air in the cavity was completely exhausted. Carbonization was carried out in an argon atmosphere in a tubular furnace. Finally, the carbonization temperature program was set: initially 5 °C min -1 The heating rate was raised to 1000℃, kept at this temperature for 2h, and finally heated at 5℃min -1 The rate of cooling is reduced to room temperature, and the NC-1000 hard carbon material (nitrogen-doped glucose-based hard carbon material) is taken out after the cavity is cooled; Step (4) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for later use. The red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then freeze-dried and transferred to a glove box. The special anhydrous and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. The red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. An ideal molar ratio of 4:3 (Sn:P) is used to calculate and use an electronic balance to weigh the Sn and P elemental powders and place them for later use. Then, zirconium beads with a diameter of 5 mm are weighed at a ball-to-material ratio of 20:1, and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protective process. Finally, the parameters of the micro planetary ball mill are set as follows: the motor speed is selected to be 600 rpm, and the intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 24 hours. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use. Step (5) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1. Sn4P3 and nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2. Under the condition that the ratio remains unchanged, the pyrolysis temperature of the hard carbon is changed, that is, Sn4P3:NC-1000=8:2. The ball mill is sealed and filled with inert gas for a protection process, and then sealed and ventilated. Finally, the power is turned on, the motor speed is selected to be 500 rpm, and an intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 4 hours, to obtain Sn4P3@NC composite glucose-based hard carbon material. Comparative Example 1
[0027] Step (1) Preparation of glucose-based hard carbon precursor 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and water were added to a stainless steel autoclave at a mass ratio of 15:85 (i.e., 56.67 g of water), and hydrothermally reacted at 240 ° C for 4 hours, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor 0.04 g of the glucose-based hard carbon precursor prepared in step (1) was dissolved in 80 mL of deionized water, stirred vigorously at room temperature, and then 120 μl of formaldehyde solution was added dropwise, stirred at room temperature for 60 min, and then 0.6 g of tannic acid (TA) was slowly added, stirred at room temperature for 24 h, collected by high-speed centrifuge, washed with deionized water 3 times, and then transferred to a freeze dryer for drying for 24 h. Then, carbonization was carried out in a high-temperature tubular heating furnace, nitrogen was introduced as a protective gas, the carbonization temperature was 1200 ° C, the insulation time was 2 h, and the carbonization heating rate was 2 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor is obtained; Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) was ground into powder and placed in a crucible. After installation, the vent valve was opened and inert gas (argon) was slowly introduced for 15 minutes to ensure that the air in the cavity was completely exhausted. Carbonization was carried out in an argon atmosphere in a tubular furnace. Finally, the carbonization temperature program was set: initially 5 °C min -1 The heating rate was raised to 1200℃, kept at this temperature for 2h, and finally heated at 5℃min -1The rate is lowered to room temperature, and the NC-1200 hard carbon material (nitrogen-doped glucose-based hard carbon material) is taken out after the cavity is cooled; Step (4) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1, and Sn4P3 and the nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2. Under the condition that the ratio remains unchanged, the pyrolysis temperature of the hard carbon is changed, that is, Sn4P3:NC-1200=8:2, the ball mill is sealed and filled with inert gas for a protection process, and a sealing and ventilation treatment is performed. Finally, the power is turned on, the motor speed is selected to be 500 rpm, and an intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 4 hours, to obtain the Sn4P3@NC composite glucose-based hard carbon material. Comparative Example 2
[0028] Step (1) Preparation of glucose-based hard carbon precursor 2.5 g of glucose and 7.5 g of water were mixed to obtain a 25% glucose solution, and the 25% glucose solution and water were added to a stainless steel autoclave at a mass ratio of 15:85 (i.e., 56.67 g of water), and hydrothermally reacted at 240 ° C for 4 hours, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate was dried in a forced air drying oven for 24 hours to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor 0.04 g of the glucose-based hard carbon precursor prepared in step (1) was dissolved in 80 mL of deionized water, stirred vigorously at room temperature, and then 120 μl of formaldehyde solution was added dropwise, stirred at room temperature for 60 min, and then 0.6 g of tannic acid (TA) was slowly added, stirred at room temperature for 24 h, collected by high-speed centrifuge, washed with deionized water 3 times, and then transferred to a freeze dryer for drying for 24 h. Then, carbonization was carried out in a high-temperature tubular heating furnace, nitrogen was introduced as a protective gas, the carbonization temperature was 1400 ° C, the insulation time was 2 h, and the carbonization heating rate was 2 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor is obtained; Step (3) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) is placed at room temperature for later use. The red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then freeze-dried and transferred to a glove box. The special water-free and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. The red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. An ideal molar ratio of 4:3 (Sn:P) is used to calculate and use an electronic balance to weigh the Sn and P elemental powders and place them for later use. Then, zirconium beads with a diameter of 5 mm are weighed at a ball-to-material ratio of 20:1, and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protective process. Finally, the parameters of the micro planetary ball mill are set as follows: the motor speed is selected to be 600 rpm, and the intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 24 hours. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use. Step (4) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (3) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (2) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1. Sn4P3 and nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2. Under the condition that the ratio remains unchanged, the pyrolysis temperature of the hard carbon is changed, that is, Sn4P3:NC-1400=8:2. The ball mill is sealed and filled with inert gas for a protection process, and then sealed and ventilated. Finally, the power is turned on, the motor speed is selected to be 500 rpm, and an intermittent working mode is adopted: work for 2 hours, rest for 30 minutes, and the effective working time is 4 hours, to obtain Sn4P3@NC composite glucose-based hard carbon material.
[0029] Comparison of detection experiments: The Sn4P3@NC composite glucose-based hard carbon materials obtained in Examples 1 to 4 and the comparative products 1 and 2 were tested. The specific testing method is as follows: Constant current charge and discharge test Constant current charge and discharge test is an important means for characterizing battery performance, mainly including long cycle test, short cycle low current cycle test, rate test, charge and discharge efficiency, etc. After the sodium ion battery assembled in the present invention was stationary for 24 hours, a series of cycle performance tests were carried out using the Xinwei battery test system. The test voltage range is 0.01V-3.0V.
[0030] X-ray Photoelectron Spectroscopy X-ray photoelectron spectroscopy (XPS) mainly analyzes the state of elements and bonding composition on the surface of materials. The functional groups on the surface of carbon materials are particularly important for sodium-ion batteries, and different functional groups play different roles and exert different effects. XPS specifically analyzes the bonding state and composition of the surface of carbon materials, and determines the specific content changes of each functional group through the characteristic peak area.
[0031] Table 1 First discharge specific capacity test results
[0032] Table 2 Initial charge specific capacity test results
[0033] It can be seen from Tables 1 and 2 that the charge and discharge specific capacity of Example 2 is the best. The charge and discharge specific capacity of the Sn4P3@NC composite glucose-based hard carbon material increases with the increase of the pyrolysis temperature. When the pyrolysis temperature is 800°C, the charge and discharge specific capacity reaches the highest. After 800°C, the charge and discharge specific capacity of the hard carbon material decreases with the increase of the pyrolysis temperature. In summary, the optimal pyrolysis temperature of the Sn4P3@NC composite glucose-based hard carbon material is 800°C.
[0034] Table 3 X-ray photoelectron spectroscopy test results
[0035] As shown in Table 3, the content of N-5 in Example 2 is the highest. The active sites generated by N-5 improve the electronic conductivity of the carbon material, thereby increasing the Na + The high content of N-5 was obtained by adjusting the sintering temperature and the degradation of electronic conductivity was successfully avoided, thereby improving the Na+ storage capacity of Sn4P3@NC composite glucose-based hard carbon materials. + storage performance. These oxygen-containing functional groups can participate in Na + The surface redox reaction of Na + Storage capacity. The results of the above electrochemical analysis clearly show that the Sn4P3@NC-800 composite glucose-based hard carbon material electrode has excellent performance, high reversible capacity and long cycle life. The higher N-5 ratio, porous structure, moderate defects and active sites are conducive to its excellent performance.
[0036] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A hard carbon material for a negative electrode of a sodium ion battery, characterized in that: include: Preparation of glucose-based hard carbon precursors, preparation of nitrogen-doped glucose-based hard carbon precursors, preparation of nitrogen-doped glucose-based hard carbon materials, preparation of Sn4P3 alloy nanomaterials, preparation of Sn4P3@NC composite glucose-based hard carbon materials.
2. The hard carbon material for a negative electrode of a sodium ion battery according to claim 1, characterized in that: Step (1) Preparation of glucose-based hard carbon precursor Glucose and water are mixed to obtain a glucose solution, and then the glucose solution and water are added to a stainless steel high-pressure reactor in a certain mass ratio, hydrothermally reacted at a certain temperature, naturally cooled to room temperature, washed with deionized water and filtered to neutrality, and the obtained solid precipitate is dried in a forced air drying oven to obtain a glucose-based hard carbon precursor; Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor The glucose-based hard carbon precursor prepared in step (1) is dissolved in deionized water, stirred vigorously at room temperature, then formaldehyde solution is added dropwise, stirred at room temperature, and then tannic acid (TA) is slowly added, stirred at room temperature, collected by centrifugation in a high-speed centrifuge, washed with deionized water, and then the sample is transferred to a freeze dryer for drying. Subsequently, carbonization is carried out in a high-temperature tubular heating furnace, nitrogen is introduced as a protective gas, and the carbonization temperature, holding time, and carbonization heating rate are set to finally obtain a nitrogen-containing glucose-based hard carbon precursor; Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) is ground into powder and placed in a crucible. After installation, the vent valve is opened and an inert gas (argon) is slowly introduced to ensure that the air in the cavity is exhausted. Carbonization is performed in an argon atmosphere in a tubular furnace. Finally, a carbonization heating program is set: keep warm at a certain temperature, and finally cool to room temperature at a certain rate. After the cavity is cooled, the NC-T hard carbon material (nitrogen-doped glucose-based hard carbon material) is taken out; Step (4) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for later use, the red phosphorus is subjected to a water washing process to remove surface impurities and oxides, and then transferred to a glove box after freeze drying. The special water-free and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. An appropriate amount of red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for later use. Using an ideal molar ratio, a certain mass ratio of Sn and P elemental powders is calculated and weighed using an electronic balance and placed for later use. Then, zirconium beads are weighed according to the mass of the ball-to-material ratio and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protection process. Finally, the parameters of the micro planetary ball mill are set. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for later use. Step (5) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a certain ball-to-material mass ratio, and Sn4P3 and the nitrogen-doped glucose-based hard carbon precursor are compounded in a certain mass ratio. Under the condition of keeping the ratio unchanged, the pyrolysis temperature of the hard carbon is changed, the ball mill is sealed and filled with inert gas for protection process, and then sealed and ventilated. Finally, the power is turned on, and after working for a certain period of time, the Sn4P3@NC composite glucose-based hard carbon material is obtained.
3. The hard carbon material for a negative electrode of a sodium ion battery according to claim 2, characterized in that: Step (1) Preparation of glucose-based hard carbon precursor Mix 2.5-3g of glucose and 7.5-8g of water to obtain a 25-30% glucose solution, then add the 25-30% glucose solution and water in a mass ratio of 15:85-20:90 (i.e. 56.67-61.2g of water) into a stainless steel high-pressure reactor, perform hydrothermal reaction at 240-260°C for 4-5 hours, cool naturally to room temperature, wash with deionized water and filter to neutrality, and dry the obtained solid precipitate in a forced air drying oven for 24-28 hours to obtain a glucose-based hard carbon precursor.
4. The hard carbon material for a negative electrode of a sodium ion battery according to claim 3, characterized in that: Step (2) Preparation of nitrogen-doped glucose-based hard carbon precursor Take 0.04-0.06 g of the glucose-based hard carbon precursor prepared in step (1) and dissolve it in 80-100 mL of deionized water. Stir vigorously at room temperature, then drop 120-150 μl of formaldehyde solution, stir at room temperature for 60-80 min, then slowly add 0.6-0.8 g of tannic acid (TA), stir at room temperature for 20-24 h, collect by high-speed centrifuge, wash with deionized water 3-4 times, and then transfer the sample to a freeze dryer for drying for 24-26 h. Then, carbonize it in a high-temperature tubular heating furnace, introduce nitrogen as a protective gas, the carbonization temperature is 700-1400 ° C, the insulation time is 2-2.5 h, and the carbonization heating rate is 2-3 ° C min -1 , and finally a nitrogen-containing glucose-based hard carbon precursor was obtained.
5. The hard carbon material for a negative electrode of a sodium ion battery according to claim 4, characterized in that: Step (3) Preparation of nitrogen-doped glucose-based hard carbon material The nitrogen-doped glucose-based hard carbon precursor prepared in step (2) was ground into powder and placed in a crucible. After installation, the vent valve was opened and inert gas (argon) was slowly introduced for 15-20 minutes to ensure that the air in the cavity was exhausted. Carbonization was carried out in an argon atmosphere in a tubular furnace. Finally, the carbonization temperature program was set: initially 4-5 °C min -1 The heating rate is raised to 800-900℃, kept at this temperature for 1-2h, and finally heated at 4-5℃min -1 The temperature of the cavity was cooled to room temperature at a rate of 700-1400°C. After the cavity was cooled, the NC-T hard carbon material (nitrogen-doped glucose-based hard carbon material) was taken out. Under the same carbonization steps, NC-T hard carbon materials were prepared at pyrolysis conditions of 700-1400°C.
6. The hard carbon material for a negative electrode of a sodium ion battery according to claim 5, characterized in that: Step (4) Preparation of Sn4P3 alloy nanomaterials The nitrogen-doped glucose-based hard carbon precursor prepared in step (3) is placed at room temperature for use. The red phosphorus is washed with water to remove impurities and oxides on the surface. After freeze-drying, it is transferred to a glove box. The special water-free and oxygen-free environment of the glove box is used to prevent the red phosphorus from being rapidly oxidized and burned or converted into white phosphorus during the grinding process. The red phosphorus is placed in a mortar and ground to obtain red phosphorus powder, which is sealed for use. The ideal molar ratio of 4:3-6:5 (Sn:P) is used to calculate and use an electronic balance to weigh the Sn and P elemental powders and place them for use. Then, zirconium beads with a diameter of 5-6 mm are weighed at a ball-to-material ratio of 20:1-40:3, and placed in a ball mill. The ball mill is sealed and filled with inert gas for a protective process. Finally, the parameters of the micro planetary ball mill are set, and the motor speed is selected to be 600-800 rpm. The intermittent working mode is adopted: work 2-3 hours, rest 30-45 minutes, and the effective working time is 24-30 hours. After the program is completed, the cavity is allowed to cool naturally to room temperature before the Sn4P3 raw material is taken out for use.
7. The hard carbon material for a negative electrode of a sodium ion battery according to claim 6, characterized in that: Step (5) Preparation of Sn4P3@NC composite glucose-based hard carbon material The Sn4P3 alloy nanomaterial prepared in step (4) and the nitrogen-doped glucose-based hard carbon precursor prepared in step (3) are weighed in proportion, and zirconium beads and raw materials (Sn4P3+nitrogen-doped glucose-based hard carbon precursor) are weighed in a ball-to-material mass ratio of 20:1-40:3, and Sn4P3 and nitrogen-doped glucose-based hard carbon precursor are compounded in a mass ratio of 8:2-11:
4. Under the condition that the ratio remains unchanged, the pyrolysis temperature of the hard carbon is changed, the ball mill is sealed and filled with inert gas for protection process, and sealing and ventilation treatment are performed. Finally, the power is turned on, the motor speed is selected to be 500-600rpm, and an intermittent working mode is adopted: work 2-3h, stop 30-45min, and the effective working time is 4-5h, to obtain Sn4P3@NC composite glucose-based hard carbon material.
